The Characteristics of the Repair Cost Distribution in Apartment Housing - Lee, KangHee; Chae, ChangU (KIEAE Journal, 2015)
Purpose: The repair would require to conserve and improve the building function and performance since built. Each household is responsible for maintaining the public facilities and paying the required cost. Therefore, it needs to get the tool or method to forecast the required cost in the future. Before the repair cost is provided, it needs to catch the repair cost distribution and provide the unit cost for the repair cycle. In this study, it aimed at providing the repair cost unit and analyzing the repair cost distribution in a roof proofing work, elevator work and building painting, which are divided into a fully work and partly change. Results of this study are shown that first, the average repair cost for roof proofing work is provided with 166.59×103 won/household and 1.59×103 won/㎡ of a full change, 33.22×103 won/household and 0.33×103won /㎡ for a partly work. In addition, elevator work is 557.45×103won /household and 5.38×103won /㎡ for a full change, 32.92×103won /household and 0.56×103won /㎡ for a partly repair. Painting has a 304.48×103won /household and 2.94×103 won/㎡. Second, the distribution pattern of repair unit cost has a weibull-typed distribution which has a long tail to the right. KCI Citation Count: 0